2016
DOI: 10.1523/jneurosci.2837-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Spatial Thermal Gradient Encoded in Thermosensory Neuron AFD inCaenorhabditis elegans

Abstract: During navigation, animals process temporal sequences of sensory inputs to evaluate the surrounding environment. Thermotaxis of Caenorhabditis elegans is a favorable sensory behavior to elucidate how navigating animals process sensory signals from the environment. Sensation and storage of temperature information by a bilaterally symmetric pair of thermosensory neurons, AFD, is essential for the animals to migrate toward the memorized temperature on a thermal gradient. However, the encoding mechanisms of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 37 publications
(34 reference statements)
9
46
0
Order By: Relevance
“…Second, after locating the T c , cryophilic migration ceases and animals track precisely along the T c within the gradient. The AFD sensory neuron is the principal receiver, encoder, and transducer of ambient temperature changes in C. elegans (22,25,27). Signals generated in AFD are transmitted to the postsynaptic AIY interneuron and indirectly to secondary interneurons for processing and integration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, after locating the T c , cryophilic migration ceases and animals track precisely along the T c within the gradient. The AFD sensory neuron is the principal receiver, encoder, and transducer of ambient temperature changes in C. elegans (22,25,27). Signals generated in AFD are transmitted to the postsynaptic AIY interneuron and indirectly to secondary interneurons for processing and integration.…”
Section: Methodsmentioning
confidence: 99%
“…Candidate and AWC neurons suggested that PKC-2 is involved in thermotaxis. AFD directly mediates temperature perception and controls a circuit that governs thermotaxis (25,27). AWC principally mediates responses to odorants (28).…”
mentioning
confidence: 99%
“…Because the mathematical models in these studies usually describe changes in the concentrations of signaling molecules, the LP measure should be useful for comparisons of simulations and experiments. In the computational data analyses of FRET imaging, dynamical relationships between molecular activity and certain biological outputs, e.g., membrane protrusion in our example ( Fig 4 ), have been examined via cross-correlation analysis [27, 31, 32], and intracellular signal transfer from the molecular activity to the biological output has been identified as the response function [33, 34]. In these analyses, the LP measure could be favorable for avoiding signals that are biasedly amplified by the ratiometric measure ( Fig 3D ).…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated by Kobayashi and collaborators, showing that cultured AFD neurons harbor all of the necessary machinery to store and update a thermal memory [42 ], although ex vivo responses were more variable than in vivo responses. In another study, the same group showed that in worms navigating in a continuous temperature gradient, the combination of motion-imposed thermal variations and short-term adaptation properties produced intermittent activity peaks in AFD [43]. Discrete AFD activity events correlated with turns in well-fed, but not starved animals.…”
Section: Thermosensory Plasticitymentioning
confidence: 94%
“…However, it seems that FLP in cmk-1 mutants has at least superficially intact thermo-detection abilities and that CMK-1 signaling might rather adjust the nature or the degree of neurotransmission to secondary neurons. This situation might be reminiscent of the apparent uncoupling between thermosensation and behavior observed upon starvation in AFD [43]. …”
mentioning
confidence: 95%